Cultural Origins of Preventive Health Care Utilization - Jan Bietenbeck; Lukas Maschmann; Therese Nilsson; Devon Spika (Institute of Labor Economics (IZA), 2025)
We examine whether culturally transmitted time and risk preferences help explain differences in preventive health care uptake. We combine individual-level survey data from 27 European countries with country-level preference measures from the Global Preferences Survey. To isolate cultural influences from institutional and economic confounders, we focus on second-generation immigrants, who were born and currently reside in the same country – and thus face the same institutional environment and health care system – but whose parents originate from culturally distinct countries. We find that descendants of more patient cultures are more likely to use preventive services, while those from more risk-taking cultures are less likely to do so. These associations appear across multiple preventive care outcomes and remain robust to a wide range of socio-demographic and country-of-origin controls. The results highlight the role of culturally shaped preferences as a subtle but systematic determinant of preventive health behavior.
Keywords: 330; preventive care; culture; patience; risk-taking